Biopetrol synthesized from rubber seed's fatty acid using fuller's earth as catalyst - Nur Liyana, Nasrudin (2010)
Ever since it was known that fossil fuel are finite, scientists has been looking for alternative energy to replace fossil fuel. Biopetrol mostly derived from vegetable oils and hence it can be categories as a renewable fuel. However the usage of vegetable oil for biopetrol will put a pressure onto the food demands and its best to be ease by using new and unexploited oil crops capable of producing fats and oil for the industry where in this topic, rubber seed. The main objective is to synthesize biopetrol from fatty acids obtain from rubber seeds via catalytic cracking using fuller earth as catalyst. Long chain of fatty acid will be break down into smaller chain. The process is done by extracting oil from rubber seed via soxhlet extraction method using hexane as the extractor. The excess hexane is removed by using rotary evaporator and the extracted purified oil is then mixed together with fuller earth and continuously heated and stir for 2hours. Rubber seed oil that has been cracked with 20g fuller’s earth is then diluted into 4 different mixtures with hexane as solvent-1%, 5%, 10%, 20%. About 1.5 ml of each sample is injected trough 0.2 through 0.2μm syringe filter into each vials which contains mixture samples before proceed to analyzing using gas chromatography. Isooctane obtained is around 64%- 111% in Rubber seed extracted by using fuller earth. This is due to various factor such as random reaction in catalytic cracking, porosity property of fuller earth, unmodified gc peak area that cause the existence of impurities and contamination of the apparatus. Isoocatane can be successfully synthesis from rubber seed by using fuller earth as catalyst.